PENGARUH PENDAPATAN DAN GAYA HIDUP TERHADAP PERILAKU KONSUMTIF PADA MAHASISWA JURUSAN PENDIDIKAN ILMU PENGETAHUAN SOSIAL FKIP UNIVERSITAS RIAU - Sutriati Sutriati; Sri Kartikowati; RM Riadi RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Today’s economic growth is experiencing a very rapid development. This is accompanied by increasing levels of consumption among the community. Consumption seems to lose its function, consumption is no longer to meet the needs, but to fulfill the desire. Attitudes are caused by income and lifestyle factors. Any income earned is no longer used as per its function. The main need as a student is forgotten, the income earned never feels enough and in the end they will do all kinds of ways to fulfill that desire. The purpose of this study is to determine the effect of income and lifestyle on consumtive behavior of Social Science Education 2015 Departement Students of Teacher’s Training and Education Faculty of University of Riau. The type of this research is quantitative descrriptive research. The population consists of 220 respondents. By using random sampling technique, a sample of 126 respondents was taken.The data analysis technique used is multiple regression analysis R2 analysis hypothesis testing is done by pastial significant test and simultaneous significant test. The result of the research shows that the coefficient of determination (R2) is 54,2% which means 54,2% of consumptive behavior influenced by income and lifestyle while 45,8% is influenced by other independent variable not included in this research. Therefore, for further research in order to add other variables besides the two independent variables in this study. Next, be a wise consumer who is able to distinguish between wants and needs.Keywords: Income, Lifestyle, Consumptive